2017
DOI: 10.1097/aci.0000000000000348
|View full text |Cite
|
Sign up to set email alerts
|

Childhood asthma is a risk factor for the development of chronic obstructive pulmonary disease

Abstract: Purpose of Review This review will catalog the many recent longitudinal studies that have investigated the relationship between asthma and lung function, or the persistence and trajectories of lung function deficits. Recent Findings Recent work has reported on 50-year follow-ups of some prominent population cohorts. A history of asthma confers a 10-to-30 fold risk of chronic obstructive pulmonary disease. Subjects reaching a reduced maximum growth of FEV1 in early adulthood are at risk for early or more seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 46 publications
0
46
0
1
Order By: Relevance
“…There has been a growing interest in the risk of early life asthmatics for developing COPD, and thus ACO, in adulthood [ 15 ]. It has been proposed that in some childhood asthmatics, the risk for COPD is the result of the lungs never achieving their expected growth and development in early adulthood [ 11 , 12 , 16 , 20 , 52 , 53 ]. Normal decline in lung function can lead to COPD since expected maximal FEV 1 is never attained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a growing interest in the risk of early life asthmatics for developing COPD, and thus ACO, in adulthood [ 15 ]. It has been proposed that in some childhood asthmatics, the risk for COPD is the result of the lungs never achieving their expected growth and development in early adulthood [ 11 , 12 , 16 , 20 , 52 , 53 ]. Normal decline in lung function can lead to COPD since expected maximal FEV 1 is never attained.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood asthma is a genetically distinct asthma subtype, with estimated heritability of 68–92% [ 2 10 ]. Asthma is a known risk factor for development of reduced lung function and chronic obstructive pulmonary disease (COPD) in adults [ 11 14 ]. Asthmatics are often excluded from COPD studies, and thus information on the mechanism of disease and appropriate treatments for asthma-COPD overlap (ACO) remains limited [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,18 Other cohorts have shown that asthma and wheezy bronchitis are associated with COPD risk. 22 In the Childhood Asthma Management Program, 11% of 1,041 participants met spirometric criteria for COPD by age 30 years, and analysis of lung growth trajectories showed a subset with reduced lung growth. 5 The Aberdeen WHEASE cohort followed 330 subjects to age 61 years, showing that childhood asthma and wheeze were associated with COPD development.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that among a population of adult smokers, asthma in early life results in more active respiratory disease, with increased frequency and severity of exacerbations but without an increased rate of lung function decline or disease progression on chest CT scans. 22 Early-life respiratory diseases are known risk factors for the development of COPD. [1][2][3][4][5] COPD in these populations is likely due to lung development progressing along a reduced lung growth trajectory, with maximal expected FEV 1 never being achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients with NA exhibited a poor response to treatment and may have irreversible air ow obstruction [3]. A long-term cohort study has shown that children with asthma reported a 10-32-fold increased risk of developing adult COPD which was also characterized by airway neutrophilic in ammation [4]. Airway remodeling is a common pathological process of asthma and COPD and it is also an important cause of air ow limitation.…”
Section: Introductionmentioning
confidence: 99%